2022
DOI: 10.3389/fpubh.2022.1041745
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional assessment of knowledge, awareness of risk factors, and perceptions of thyroid disease (TD) among adults living in Saudi Arabia – A community based study

Abstract: BackgroundThe incidence of thyroid diseases has tripled in the last three decades, and the prevalence is rising rapidly irrespective of gender and genetics. This study aimed to assess the Knowledge, awareness of risk factors, and perceptions of thyroid disease among the Saudi Community in Saudi Arabia.MethodsA cross-sectional, online web-based, survey type study was conducted between November 2021 to January 2022 among residents living in Saudi Arabia. Individuals aged ≥ 18 years who expressed a willingness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…There were approximately 500 undergraduate students enrolled in PharmD and Nursing courses. Similar to many previous studies [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], we estimated the required sample size with a 95% CI and a 5% margin of error using an online calculator ( , last accessed on 6 January 2023). We assumed that the response distribution for each question would be 50% because we were uninformed of the probable outcomes for each question.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were approximately 500 undergraduate students enrolled in PharmD and Nursing courses. Similar to many previous studies [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], we estimated the required sample size with a 95% CI and a 5% margin of error using an online calculator ( , last accessed on 6 January 2023). We assumed that the response distribution for each question would be 50% because we were uninformed of the probable outcomes for each question.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaires for this study were adopted from previous studies [ 15 , 16 , 23 ]. The study questionnaires were divided into three sections.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, a study with 1000 participants reported varying levels of knowledge and perceptions of thyroid disease [ 6 ]. Hence, this study aimed to explore the level of knowledge of thyroid disease manifestation and its risk factors among the general population in the Tabuk region of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is generally known that today's undergraduates would become tomorrow's professionals, a thorough awareness of the clinical facts related to diseases will help them in their work and help them to give their patients the best care possible. (14)(15)(16)(17)(18)(19). Additionally, awareness of stroke would have a significant impact on morbidity and mortality rates, as well as contribute to the promotion of healthy habits.…”
Section: Introductionmentioning
confidence: 99%